How does medicine Parkon® affect the MPTP-induced oxidation stress and MAO systems of the rats brain - N Goldstein; A Kamensky; T Arshavskaya; R Goldstein (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2021)
The review of the literature seems to confirm effects of negative air ions (NAIs) on several brain functions. Indeed, a significant association between NAIs exposure and both wellbeing and high cognitive performances has been described [1-3].